A recurrent cancer-associated substitution in DNA polymerase ε produces a hyperactive enzyme - Xuanxuan Xing (Nature Portfolio, 2019)
Somatic alterations in the exonuclease domain of DNA polymerase ɛ have been linked to the development of highly mutated cancers. Here, the authors report that a major consequence of the most common cancer-associated Polɛ variant is a dramatically increased DNA polymerase activity.